LIVING QUR'AN PERSPEKTIF PENDIDIKAN ISLAM: BELAJAR DARI TRADISI KEAGAMAAN ETNIS SASAK TRANSMIGRASI DI DESA KARYA MUKTI DONGGALA SULAWESI TENGAH - ilham, Moh.; Mashuri, Saepudin; Hamzah, Erni Irmayanti; Agustan, Agustan (TA'LIM : Jurnal Studi Pendidikan Islam, 2025)
This study examines the Living Qur'an in the Religious Tradition of the Sasak Ethnic Group in Karya Mukti Village, Dampelas District, Donggala Regency from the Perspective of Islamic Education. The main focus of this study is how the implementation of the Living Qur'an in the religious tradition of the Sasak ethnic community in Karya Mukti Village is reviewed from an educational perspective, especially in forming Islamic character through the values ​​of the Qur'an. This study uses a qualitative method with a descriptive approach. Data were obtained through interviews with village heads, religious leaders, traditional leaders, and community leaders, as well as related documentation. Data collection techniques involve observation, interviews, and document analysis. The collected data are analyzed through data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of the Living Qur'an is reflected in various religious tradition practices such as completing the Qur'an, praying together, serakan, and hiziban, which are full of Qur'anic values. In addition, Islamic values ​​are also manifested in the social life of society through attitudes of tolerance, mutual cooperation, and respect for religious figures. From the perspective of Islamic education, this tradition plays an important role in the informal inheritance of Islamic values ​​that shape the religious and social character of the younger generation. Thus, the Living Qur'an is not only a spiritual symbol, but also a contextual educational medium based on local culture.